Fatigue damage at room temperature in aluminium single crystals .3. Lattice rotation - Zhai, T; Martin, J; Briggs, G; Wilkinson, A (1996)
Lattice rotation was observed in different scales in aluminium single crystals fatigued in push-pull in air at room temperature, a constant shear stress amplitude 4 MPa, zero mean stress and frequency of 20 Hz. Using the channelling contrast technique in SEM, contrast of grey and dark bands consistent in dimensions with those of PSBs was observed on the surface sectioned parallel to the Burgers vector b in an A1 single crystal after 1.2 x 106 cycles, suggesting that there was lattice misorientation (rotation or tilt) between PSBs and the matrix in the specimen. It might be caused by local net material movement due to irreversible slip or non-uniform deformation in PSBs. Lattice rotation (about 6°) always appeared between a macroband and the matrix relative to the normals of two perpendicular surfaces of the specimens, as a result of net irreversible slip in one direction of b in PSBs. Often more cracks were found in a positive macroband than a negative one. Deformation bands coarser than PSBs and smaller than macrobands were also found on the surface containing b by the scanning acoustic microscope. They deviated slightly from the direction of the PSBs and were probably formed to release the internal stresses between macrobands and the matrix due to macroband formation. The macroband effect is likely a general metallographic characteristic of unidirectional fatigue in planar-slip metal single crystals. The lattice rotation was probably one of the key factors controlling crack initiation and early propagation in the A1 single crystals. Copyright © 1996 Acta Metallurgica Inc.